Manajemen Sekolah dalam Mendorong Pendidikan Karakter melalui Kegiatan Donor Darah di Kalangan Siswa Sekolah Menengah Atas - Sulistyowati; S. Rizal Yazid; Farah Saeed (CV. Global Cendekia Inti, 2025)
This study aims to analyze the role of school management in promoting character education through blood donation activities among high school students. The research method used a mixed-methods approach. The results show that students' primary motivation in donating blood is to help others, which reflects the internalization of the values ​​of altruism and social concern. Psychological barriers, such as fear of needles and fear of fainting, are the main obstacles to blood donation practices, so innovative intervention strategies have proven effective in overcoming them. The implementation of structured blood donation activities through planning, organizing, directing, and evaluating (POAC), as well as collaboration with external parties such as the Indonesian Red Cross (PMI), successfully transformed this activity into a real character learning medium, building empathy, responsibility, discipline, and social concern.